Explaining mantras : ritual, rhetoric, and the dream of a natural language in Hindu tantra - Yelle, Robert A. (Religion in history, society & culture ;, 2003)
Explaining Mantras explores the intersection of poetry and magic in the mantras or verbal formulas of Hindu Tantra and combines the study of ancient Tantric rituals with the latest theories in the human sciences.